An investigative study of a Dubai-based mainstream private school in meeting the educational needs of a student with Dyspraxia DOC - Sheta, Yasmine (2019)
The purpose of this study is to investigate the practices of a Dubai-based mainstream school in meeting the needs of a student with Dyspraxia. The researcher used the qualitative approach which is based on the triangulation method represented in observations, questionnaire-based surveys, focus-groups, interviews and document analysis. This research paper aimed at studying the school’s policy and provision regarding students with special educational needs. The researcher covered the admission policy, the assessment, the identification process, the intervention and the curriculum. Additionally, the researcher studied the support provided to the student, including the Individual Educational Plan, and its effect on her academic achievement. Furthermore, teacher’s training was discussed in this study. The findings uncovered deficiencies between theory and practice with respect to students with Dyspraxia. The school policy and provision support inclusion while the lack of teacher training, lack of funding and the lack of resources hinder the implication of this policy. This paper suggested a set of recommendations to the school, the Ministry of Education and teachers. These suggestions aim to provide good practices for the successful inclusion of students with Dyspraxia and students with special educational needs as well. The researcher hopes that her study would be a valuable addition to the research done within the field of special education.